Breastfeeding and infant sleep patterns: an Australian population study - Islam, F.M. Amiril; Scalzo, K; McEgan, K; Galbally, M; Lewis, A (My University, 2013)
Objective: Our purpose was to determine if babies breastfed at 6 months of age were more likely to wake at night and less likely to sleep alone than formula-fed babies. Patients and Methods: Data were drawn from the first wave of The Longitudinal Study of Australian Children, an ongoing, nationally representative study of the growth and development of Australia's children. The 4507 participants met the criteria for this study. The measures examined infant sleep problems as the outcome and breastfeeding at 6 months of age as the exposure in addition to the demographic data, maternal mental health, infant birthweight and gestational age at delivery. Results: After adjustment for covariates, reports by mothers of infants that breastfed at 6 months of age suggested infants were 66% more likely to wake during the night and 72% more likely to report difficulty sleeping alone. However, breastfeeding had a strongly protective effect on wheezing, coughing, snoring and breathing problems, and it was not associated with restless sleep or problems getting to sleep for the infant. Conclusions: Breastfeeding was found to be associated with increased night waking and this is consistent with other studies. There are biological reasons why this might be required to ensure breastfeeding continues to 6 months and beyond. The current low rates of sustained breastfeeding in many Western countries needs to be reconsidered in relation to parental and public health practices promoting prolonged nocturnal infant sleep patterns.
Keywords: Child Development -- Sleep; Health -- Breastfeeding; Children -- Babies; Childhood and child development; Health and wellbeing; Health; Children; Child Development; Babies; Sleep; Breastfeeding; Childhood and child development; Health and wellbeing